Pharmacist-led hospital intervention reduces unintentional patient-generated medication discrepancies after hospital discharge - Jošt, Maja; Knez, Lea; Kos, Mitja; Kerec Kos, Mojca (Frontiers in Pharmacology, 2024)
Background: Medication reconciliation can significantly reduce clinically important medication errors at hospital discharge, but its impact on post-discharge medication management has not been investigated. We aimed to investigate the incidence of patient-generated medication discrepancies 30 days after hospital discharge and the impact of a pharmacist-led medication reconciliation coupled with patient counselling on clinically important discrepancies caused by patients.Methods: A pragmatic, prospective, controlled clinical trial was conducted at the University Clinic Golnik, Slovenia. Adult patients were divided into an intervention group and a control group. The intervention group received pharmacist-led medication reconciliation at admission and discharge, plus patient counselling at discharge. Medication discrepancies were identified by comparing the therapy prescribed in the discharge letters with the therapy 30 days after discharge, obtained through telephone patient interviews. Discrepancies were classified as intentional or unintentional, and their clinical importance was assessed.The study included 254 patients (57.9% male, median age 71 years), with 136 in the intervention group and 118 in the control group. Discrepancies occurred with a quarter of the medicines (617/2,441; 25.3%) at 30 days after hospital discharge, and patients themselves caused half of the discrepancies (323/617; 52.4%), either intentionally (171/617; 27.7%) or unintentionally (152/617; 24.6%). Clinically important discrepancies occurred in 18.7% of intentional and 45.4% of unintentional patient-generated changes. The intervention significantly reduced the likelihood of clinically important unintentional patient-generated discrepancies (OR 0.204; 95%CI: 0.093-0.448), but not clinically important intentional patient-generated discrepancies (OR 2.525;).The latter were more frequent among younger, male patients and patients hospitalized for respiratory diseases.The study emphasizes the importance of addressing discrepancies made by patients after hospital discharge, which can result in potentially harmful outcomes. It also shows that a pharmacistled hospital intervention can significantly reduce discrepancies in the early post-discharge period.These findings can guide the development of future services to improve patient support for medication management after hospitalization.